LIVRO DISCUTE SOBRE MORALIDADE DAS VIRTUDES E ECONOMIA DE MERCADO - Aires de Carvalho, Helder Buenos (Pensando - Revista de Filosofia, 2015)
A coletânea de essaios "Virtue and Economy: Essays on Morality and Markets", editada por Andrius Bielskis e Kelvin Knight, que inclui um capítulo de Alasdair MacIntyre, engaja-se na discussão dos pressupostos teóricos e da realidade institucional do capitalismo moderno. O livro foi lançado em Junho de 2015 pela Ashgate Co. Interest in Aristotelianism and in virtue ethics has been growing for half a century but as yet the strengths of the study of Aristotelian ethics in politics have not been matched in economics. This ground-breaking text fills that gap. Challenging the premises of neoclassical economic theory, the contributors take issue with neoclassicism’s foundational separation of values from facts, with its treatment of preferences as given, and with its consequent refusal to reason about final ends. The contrary presupposition of this collection is that ethical reasoning about human ends is essential for any sustainable economy, and that reasoning about economic goods should therefore be informed by reasoning about what is humanly and commonly good. Contributions critically engage with aspects of corporate capitalism, managerial power and neoliberal economic policy, and reflect on the recent financial crisis from the point of view of Aristotelian virtue ethics. Containing a new chapter by Alasdair MacIntyre, and deploying his arguments and conceptual scheme throughout, the book critically analyses the theoretical presuppositions and institutional reality of modern capitalism. Sumário: Introduction, Andrius Bielskis and Kelvin Knight. Part I The Virtue Critique of Capitalist Economy: The irrelevance of ethics, Alasdair MacIntyre; Neoliberalism and its threat to moral agency, Bob Brecher; Economics as ethical pre-condition of the credit crunch, William Dixon and David Wilson; Is Aristotelian capitalism possible?, Rajeev Sehgal. Part II Polemicising the Critique: Equality, vulnerability and independence, John O’Neill; No place to hide for the moral self: bureaucratic individualism and the fate of ethics in modernity, Peter McMylor; Reappraising neoliberalism: homo economicus, practitioners and practices, Mustafa Ongun; The great perverting transformation, Niko Noponen. Part III Alternatives to Capitalist Economy: Goods, interests and the language of morals, Piotr Machura; Formalising functions: the history of a passing challenge to capitalist economy, Kelvin Knight; Towards a critical ethical economy, Russell Keat; How is ethical revolution possible?, Buket Korkut Raptis; Anti-capitalist politics and labour for the twenty-first century: history and future challenges, Andrius Bielskis. Index. Sobre os editores: Andrius Bielskis is Professor of Political Theory at Mykolas Romeris University and a leading public intellectual in Lithuania. He received his PhD in Philosophy from the University of Warwick, and has taught political and moral philosophy at several British and European universities. Andrius is a founding member both of the progressive intellectual and political movement New Left 95 and of the DEMOS Institute of Critical Thought. Kelvin Knight is Reader in Ethics and Politics at London Metropolitan University, Director of its Centre for Contemporary Aristotelian Studies in Ethics and Politics (CASEP), course leader of its MA in International Human Rights and Social Justice, General Secretary of the International Society for MacIntyrean Enquiry, and Secretary of the Contemporary Aristotelian Studies specialist group of the UK Political Studies Association.